2014
DOI: 10.1177/2047487314558771
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation product and incident cardiovascular events in a normal weight population: Tehran Lipid and Glucose Study

Abstract: LAP is an independent predictor of cardiovascular events in normal BMI subjects, but is not superior over other anthropometrics indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 38 publications
1
38
1
1
Order By: Relevance
“…Other groups such as Depres [25] reported that WC in combination with fasting triglycerides can be used to identify people with "hypertriglyceridemia-waist phenotype", the results of which are in agreement with other researchers who have demonstrated a strong association between the aforementioned phenotype and the risk of coronary artery disease [26,27].…”
Section: Introductionsupporting
confidence: 86%
“…Other groups such as Depres [25] reported that WC in combination with fasting triglycerides can be used to identify people with "hypertriglyceridemia-waist phenotype", the results of which are in agreement with other researchers who have demonstrated a strong association between the aforementioned phenotype and the risk of coronary artery disease [26,27].…”
Section: Introductionsupporting
confidence: 86%
“…In addition, it has been reported that although LAP was an independent predictor of cardiovascular events even in normal weight subjects, it had no advantageous capabilities over other anthropometrics indices . Similarly, Dai et al .…”
Section: Discussionmentioning
confidence: 97%
“…Even though a large number of studies in adult population indicate VAI and LAP as reliable markers of cardiometabolic risk advantageous over BMI and WC, there are another ones that report the opposite …”
Section: Introductionmentioning
confidence: 97%
“…Chiang et al16 reported that LAP had significantly higher predictability than other obesity indices for prediction of metabolic syndrome among Taiwanese population older than 50 years of age. Additionally, Hosseinpanah et al36 concluded that LAP was an independent predictor of cardiovascular disease among individuals with normal BMI. Conversely, BMI, high C-reactive protein, and insulin resistance were better than LAP for the prediction of prediabetic status and cardiovascular risk in women with polycystic ovary syndrome 37.…”
Section: Discussionmentioning
confidence: 99%